What do they really think? the repertory grid technique as an educational research tool for revealing tacit cognitive structures. Issue 6 (13th April 2021) - Rozenszajn, Ronit; Kavod, Galia Zer; Machluf, Yossy
ABSTRACT: The Repertory Grid Technique (RGT) is a qualitative method, based on the Personal Construct Psychology (PCP) theory, which provides a powerful tool to elicit tacit personal construction systems, with minimal intervention and interpretation. Although the contributory potential of the RGT as a cognitive research tool in science education has been documented, few researchers are familiar with it. In this article we describe in detail the principles and steps of the RGT, and how it can be utilised, including practical recommendations and analyzed examples. We illustrate how different studies in science education have utilised the diverse models of the RGT to address different research questions, and its advantages and contribution to the field. We hope to open a window to the PCP theory and the use of the RGT as a profound method for science education research, which may have implications for teaching and learning processes.